Chromosome banding homologies of a tandem fusion in river, swamp, and crossbred buffaloes (bubalus bubalis) - Bongso, T. A.; Hilmi, M. (NRC Research Press, 1982)
The chromosomes of the Murrah (River), Swamp (Malaysian kerbau), F1 hybrid (Murrah × Swamp) and first generation backcross (F1 hybrid female × Murrah male) buffaloes (Bubalus bubalis L.) were studied using Giemsa (G) and centromeric (C) banding techniques. The diploid chromosome number for the Murrah was 2n = 50, Swamp 2n = 48, F1 hybrid 2n = 49 and two backcross animals had 2n = 49 and 2n = 50, respectively. The largest two metacentric chromosomes of the Swamp resulted from a tandem fusion between the two chromosomes 4p and 9, respectively, of the Murrah karyotype. The F1 hybrid (2n = 49) and one of the backcrosses (2n = 49) had karyotypes intermediate to the Murrah and Swamp parents. The C banding patterns were useful in identifying the X and Y chromosomes of the buffalo and demonstrated that a major portion of the centromere region of chromosome 9 was not incorporated into chromosome 4 during the tandem fusion.